The Adverse Selection – Implications For Indian Stock Markets (Journal of Namibian Studies : History Politics Culture, 2023)
Liquidity reflects the financial health of a market. Bid Ask Spread is one of the important measures of liquidity. It is also an indicator of the financial stability of the stock markets. It arises as the compensation for various costs involved when trading in securities. These costs are classified as Order Processing Costs, Inventory Holding Costs and Adverse Selection Costs.